Hubungan Ketahanan Keluarga dengan Perilaku Remaja di SMAN 2 Tambun Selatan - Salma Nur Shohimah (2021)
A high level of family resilience is one of the factors that can be a reference for adolescents in undergoing a period of growth and development towards more positive behavior. This study aims to determine the relationship between family resilience and adolescent behavior at SMAN 2 Tambun Selatan. The method used is descriptive analytic with a cross-sectional design. Analysis of the data used is the Chi Square test. The questionnaire used is the standard questionnaire for family resilience, namely the FRAS (family resilience assessment scale) developed by (Xibey, 2005) with 54 questions, and the psychological behavioral psychology scale concept questionnaire developed by (Wardani, 2016) which contains 28 questions. The sampling technique used simple random sampling with a total sample of 156 students, indicating that 80 adolescents (51.3%) had a high level of family resilience with positive behavior, 13 adolescents (8.3%) had low family resilience with 63 adolescents. (40.4%) behaved negatively. The results of this study indicate that there is a relationship between family resilience and adolescent behavior (p value = 0.000), it can be seen that a high level of family resilience can affect adolescent behavior positively or negatively. Adolescents should be more open to family and more selective in relationships outside the family environment. Families should establish open communication and involve adolescents in solving existing problems together so that when the teenagers find a problem they can solve it and can behave more positively than negatively. Keywords : Family Resilience, Behavior, Teenagers.